2022
DOI: 10.1002/cssc.202102532
|View full text |Cite
|
Sign up to set email alerts
|

Promoted Hydrogenolysis of Furan Aldehydes to 2,5‐Dimethylfuran by Defect Engineering on Pd/NiCo2O4

Abstract: Catalytic hydrogenolysis of biobased furan aldehydes (i. e., 5methylfurfural, 5-hydroxymethylfurfural) to 2,5-dimethylfuran has gained extensive interest for biomass-derived fuels and chemicals. Herein, a class of NiCo 2 O 4 -supported palladium with considerable oxygen defects was synthesized by hydrogen plasma etching and phosphating methods. The oxygen defects not only promoted the hydrogenation of the C=O group but also enhanced the accessibility of coordinatively unsaturated metal cations with Lewis acidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In situ attenuated total reflection infrared spectroscopy (ATR‐IR) was used to elucidate the underlying molecular mechanism. When interacting with Pd/NUS and Pd/C, C=O group peaks redshifted from 1668 cm −1 to 1642 cm −1 over Pd/NUS, and to 1649 cm −1 over Pd/C (Figure 5D) [62, 63] . However, the position of the furan ring group is invariable at 1043 cm −1 over Pd/NUS, but redshifted to 1020 cm −1 over Pd/C.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In situ attenuated total reflection infrared spectroscopy (ATR‐IR) was used to elucidate the underlying molecular mechanism. When interacting with Pd/NUS and Pd/C, C=O group peaks redshifted from 1668 cm −1 to 1642 cm −1 over Pd/NUS, and to 1649 cm −1 over Pd/C (Figure 5D) [62, 63] . However, the position of the furan ring group is invariable at 1043 cm −1 over Pd/NUS, but redshifted to 1020 cm −1 over Pd/C.…”
Section: Resultsmentioning
confidence: 97%
“…When interacting with Pd/NUS and Pd/C, C=O group peaks redshifted from 1668 cm À 1 to 1642 cm À 1 over Pd/NUS, and to 1649 cm À 1 over Pd/C (Figure 5D). [62,63] However, the position of the furan ring group is invariable at 1043 cm À 1 over Pd/NUS, but redshifted to 1020 cm À 1 over Pd/C. The results indicate that both the furan ring and C=O groups of 5-HMF are adsorbed, activated, and hydrogenated on the Pd/C surface, but only C=O group interact with MOF-based catalyst, which ensures the highly efficient preparation of 2,5-BHMF and inhibits the formation of BTHMF.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, a recent work found that the CÀ O bond cleavage of 2,5-bis(alkoxymethyl)furans is easier and faster than the respective diols; thus, the hydrogenolysis was promoted in this reaction. [37] In order to investigate the role of temperature and promote the hydrogenation respect to the hydrogenolysis, the temperature was decreased to 80 °C, keeping the pressure at 60 bar (Figure 7B). Under these second reaction conditions, the conversion of BEMF was slowed down and the formation of…”
Section: Synthesis Of Bemthfmentioning
confidence: 99%
“…With the depletion of non-renewable fossil resources, research on the manufacturing of bio-based alternative fuels and chemicals from biomass renewables is receiving increasing attention. 5-Hydroxymethylfurfural (5-HMF), obtained efficiently from the dehydration of carbohydrates at a laboratory scale, is considered to be a very important platform chemical due to its versatile structure, which can be transformed into various valued derivatives, such as 2,5-diformylfuran, 1,2 2,5dihydroxymethylfuran, 3,4 2,5-bis(aminomethyl)furan, [5][6][7] 2,5dimethylfuran, 8,9 and 2,5-furandicarboxylic acid. 10 Therefore, recent efforts on the pilot-scale production of 5-HMF mainly focus on the contrivance of acid catalysts and the development of solvent phase systems for the dehydration of fructose.…”
Section: Introductionmentioning
confidence: 99%
“…Acid catalysts play a vital role in the catalytic conversion of fructose to 5-HMF, and can be briefly classified into ionic liquids, solid acids, transition metal salts, and mineral acids. Although the former three are widely investigated and considered environmentally benign, 8,11,12 they are not applicable for industrial utilization due to their high cost, unsatisfactory catalytic performance, and separation problems. In contrast, inorganic mineral acids are considered a mainstream catalyst for the large-scale production of 5-HMF with high efficiency and affordability.…”
Section: Introductionmentioning
confidence: 99%